1999
DOI: 10.1097/00004872-199917030-00019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of losartan on human platelet activation

Abstract: Losartan decreased platelet aggregation by a thromboxane A2-dependent mechanism. EXP 3174 was less potent than losartan in reducing thromboxane A2-dependent platelet activation. Captopril and exogenous angiotensin II had no effect on human platelet activation. These results suggest that losartan reduced thromboxane A2-dependent platelet activation independently of its effect on angiotensin II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 17 publications
5
43
0
1
Order By: Relevance
“…36 Several angiotensin receptors blockers demonstrate not profound, but still evident antiplatelet effect. 10,37,38 Aliskiren ((2(S),4(S),5(S),7(S)-N-(2-carbamoyl-2-methylpropyl)-5-amino-4-hydroxy-2,7-di-isopropyl-8-[4-methoxy-3-(3-methoxypropoxy)phenyl]-octanamid hemifumarate)), an octanamide, is the first representative of a new class of completely nonpeptide, low molecular weight, orally active transition state renin inhibitors. 39 Aliskiren effectively reduces blood pressure in patients with arterial hypertension 40,41 regardless of their racial origin, 42 and reduces production of angiotensin I-II in a dosedependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…36 Several angiotensin receptors blockers demonstrate not profound, but still evident antiplatelet effect. 10,37,38 Aliskiren ((2(S),4(S),5(S),7(S)-N-(2-carbamoyl-2-methylpropyl)-5-amino-4-hydroxy-2,7-di-isopropyl-8-[4-methoxy-3-(3-methoxypropoxy)phenyl]-octanamid hemifumarate)), an octanamide, is the first representative of a new class of completely nonpeptide, low molecular weight, orally active transition state renin inhibitors. 39 Aliskiren effectively reduces blood pressure in patients with arterial hypertension 40,41 regardless of their racial origin, 42 and reduces production of angiotensin I-II in a dosedependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…[36][37][38][39][40] 28,30,33 and especially in elderly patients with isolated systolic hypertension. 29,31 Other mechanisms by which ARBs could reduce the incidence of new or recurrent stroke include the beneficial effects of some ARBs on blood glucose control by increasing insulin sensitivity, 49,50 their platelet antiaggregating effects, [51][52][53][54] their hypouricemic effects 66,67 and their atrial antifibrillatory effects. [69][70][71] All these actions of ARBs could add to their AII-mediated stroke protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental studies have shown that losartan interacts with the TXA 2 /PGH 2 receptor in human platelets and also platelet activation by the TXA 2 agonist U46619 was significantly inhibited by losartan dosedependently. 51 Losartan also blocks the action of P-selectin on platelet adhesion. P-selectin is an adhesion protein that is stored in the alpha granules of platelets, and platelets from SHR-SP have a higher expression of P-selectin and a higher ability to adhere to synthetic and endothelial surfaces than platelets from normotensive WKY rats.…”
Section: Aii-mediated Effects Of Arbsmentioning
confidence: 99%
“…9 Both telmisartan and losartan have platelet antiaggregatory activity that is not shared by valsartan's, candesartan's, or losartan's major metabolite, EXP3174. [10][11][12][13] Losartan also reduces uric acid, an end-product of purine metabolism linked to the progression of renal disease 14 and increased CV risk 15 and implicated in the development of hypertension in children. 16 It has been hypothesized that these pleiotropic effects of specific ARBs could contribute to the lower incidence of stroke than predicted by BP reduction in outcomes trials of hypertensive patients treated with ARBs compared with treatment with other antihypertensive drugs.…”
Section: Pharmacologic Actions Unique To Specific Arbsmentioning
confidence: 99%